Functional Position Equalization and Performance Improvement in Samarinda Government: Penyesuaian Posisi Fungsional dan Peningkatan Kinerja di Pemerintah Kota Samarinda - Risdayanti Risdayanti; Titin Ruliana; Meiki Permana (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Bureaucratic reform in Indonesia emphasizes simplifying organizational structures and improving the professionalism of civil servants through the Functional Position Equalization Policy. Specific Background: This policy converts structural positions at echelons III and IV into competency-based functional roles, requiring employees accustomed to hierarchical systems to adapt to performance-based frameworks, influencing motivation and job satisfaction. Knowledge Gap: Despite the implementation of this policy, the Samarinda City Government’s SAKIP rating has remained stagnant at grade B from 2022 to 2023, indicating limited improvement in organizational performance. Aims: This study investigates how the functional position equalization policy affects organizational performance, with work motivation and job satisfaction as mediating variables. Results: Using a quantitative cross-sectional design with data from 118 respondents analyzed via SEM–WarpPLS, findings reveal that the policy significantly enhances performance, with work motivation acting as a full mediator and job satisfaction as a partial mediator. Novelty: The study integrates Herzberg’s Two-Factor Theory to explain how policy-induced structural changes influence psychological factors in public organizations. Implications: Effective implementation of this policy depends on fostering intrinsic motivation and employee satisfaction to optimize public-sector performance transformation. Highlights: Policy reform enhances bureaucracy by shifting from structural to functional roles. Work motivation fully mediates the effect of policy on performance. Herzberg’s theory explains how motivation and satisfaction drive public-sector success. Keywords: Functional Position Equalization, Work Motivation, Job Satisfaction, Organizational Performance, Herzberg’s Theory